Evolusi Pemikiran dan Lingkungan yang Berubah menuju Knowledge Base Society: Sudut Pandang Ekonomi Pancasila - Idrus Taba (Badan Pembinaan Ideologi Pancasila, 2024)
The past century has seen a significant evolution in human development, with the rise of the concept of human capital and the role of organizations in achieving this goal. The Indonesian Economic Outlook 2004 highlights the importance of human capital in the country's economic development, including the transition to a zero-carbon economy, the promotion of good governance, and the development of a knowledge-based society. Organizational management has evolved over time, with theories such as individualism and sosialism emerging. The modern era of management, from 1910 to 1930, focused on micro and macro management, with a focus on individual productivity and organizational structure. The leading management style, also known as